H = ∫ − 1 1 ( 1 + 2 x 2 x tan 2 ( x ) + 1 + 3 x 3 x tan 4 ( x ) ) d x
If H can be represented as:
D ( tan ( B π A ) ) C
where A , B , C , D are non-negative integers, find the value of A + B + C + D ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Actually this one's noT hot :D easy !
Log in to reply
I didn't find any suitable title for this problem :D
Note that:
I 1 = ∫ − 1 1 1 + 2 x 2 x tan 2 x d x = 2 1 ∫ − 1 1 ( 1 + 2 x 2 x tan 2 x + 1 + 2 − x 2 − x tan 2 x ) d x = 2 1 ∫ − 1 1 ( 1 + 2 x 2 x tan 2 x + 2 x + 1 tan 2 x ) d x = 2 1 ∫ − 1 1 tan 2 x d x Using identity ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x
Similarly, we have I 2 = ∫ − 1 1 1 + 3 x 3 x tan 4 x d x = 2 1 ∫ − 1 1 tan 4 x d x
Therefore,
I = ∫ − 1 1 ( 1 + 2 x 2 x tan 2 x + 1 + 3 x 3 x tan 4 x ) d x = 2 1 ∫ − 1 1 ( tan 2 x + tan 4 x ) d x = 2 1 ∫ − 1 1 tan 2 x sec 2 x d x = 6 1 tan 3 x ∣ ∣ ∣ ∣ − 1 1 = 3 tan 3 ( 1 )
⟹ A + B + C + D = 0 + 1 + 3 + 3 = 7
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = 1 + 2 x 2 x tan 2 ( x ) and g ( x ) = 1 + 3 x 3 x tan 4 ( x ) .
Now:
H = ∫ − 1 1 ( f ( x ) + g ( x ) ) d x = ∫ − 1 1 ( f ( − 1 + 1 − x ) + g ( − 1 + 1 − x ) ) d x = ∫ − 1 1 ( f ( − x ) + g ( − x ) ) d x
⇒ H = ∫ − 1 1 ( 1 + 2 x 2 x tan 2 ( x ) + 1 + 3 x 3 x tan 4 ( x ) ) d x = ∫ − 1 1 ( 1 + 2 x tan 2 ( x ) + 1 + 3 x tan 4 ( x ) ) d x
⇒ 2 H = ∫ − 1 1 ( tan 2 ( x ) + tan 4 ( x ) ) d x = ∫ − 1 1 tan 2 ( x ) sec 2 ( x ) d x
⇒ H = ∫ 0 1 tan 2 ( x ) sec 2 ( x ) d x
Let u = tan ( x ) ⇒ d u = sec 2 ( x ) d x
When x = 0 , u = 0 and when x = 1 , u = tan ( 1 ) . So:
H = ∫ 0 tan ( 1 ) u 2 d u = 3 u 3 ∣ ∣ ∣ ∣ 0 tan ( 1 ) = 3 tan 3 ( 1 )
So, A = 0 , B = 1 , C = 3 , D = 3 , A + B + C + D = 7 .